Investigation of Fats, Oils, and Grease Co-digestion With Food Waste in Anaerobic Membrane Bioreactors and the Associated Microbial Community Using MinION Sequencing - Iskander, Syeed Md; Amha, Yamrot M.; Wang, Phillip; Dong, Qin; Liu, Juhe; Corbett, Michael; Smith, Adam L. (Frontiers in Bioengineering and Biotechnology, 2021)
Co-digestion of fats, oils, and grease (FOG) with food waste (FW) can improve the energy recovery in anaerobic membrane bioreactors (AnMBRs). Here, we investigated the effect of co-digestion of FW and FOG in AnMBRs at fats mass loading of 0.5, 0.75, and 1.0 kg m-3 day-1 with a constant organic loading rate of 5.0 gCOD L-1 day-1 in both a single phase (SP) and two phase (TP) configuration. A separate mono-digestion of FW at an identical organic loading rate was used as the benchmark. During co-digestion, higher daily biogas production, ranging from 4.0 to 12.0% was observed in the two-phase methane phase (TP-MP) reactor compared to the SP reactor, but the difference was statistically insignificant (p>0.05) due to the high variability in daily biogas production. However, the co-digestion of FW with FOG at 1.0 kg m-3 day-1 fats loading rate significantly (p<0.05) improved daily biogas production in both the SP (11.0%) and TP (13.0%) reactors compared to the mono-digestion of FW. Microbial community analyses using cDNA-based MinION sequencing of weekly biomass samples from the AnMBRs revealed the prevalence of Lactobacillus (92.2 – 95.7% relative activity) and Anaerolineaceae (13.3 – 57.5% relative activity), which are known as fermenters and fatty acid degraders. Syntrophic fatty acid oxidizers were mostly present in the SP and TP-MP reactors, possibly because of the low pH and short solids retention time (SRT) in the acid phase digesters. A greater abundance of the mcrA gene copies (and methanogens) was observed in the SP and MP reactors compared to the acid phase (AP) reactors. This study demonstrates that FW and FOG can be effectively co-digested in AnMBRs and is expected to inform full-scale decisions on optimum fats loading rate.